INTELLECTUAL AGILITY DAN INNOVATIVE BEHAVIOR TERHADAP MINAT BERWIRAUSAHA GENERASI Z DI UNIVERSITAS MUHAMMADIYAH PALEMBANG - Eni Cahyani; Rohmawan Adi Pratama; Nadia Afrilliana; Yunita Febriani; Sudarta Sudarta (Universitas Veteran Bangun Nusantara, 2024)
This research uses a quantitative approach to see how intellectual agility abilities and innovation behavior influence generation Z's interest in entrepreneurship. Data was collected from 255 students at the Faculty of Economics and Business (FEB) from three management, accounting and digital business study programs at different levels. Probability sample with snowball technique using a questionnaire connected to Google Form. Data was collected and then tested for validity and reliability through classical assumption tests, multiple regression analysis, and innovation behavior. The research results show that intellectual ability and innovation behavior have a positive impact on interest in entrepreneurship. Likewise, intellectual agility and innovation behavior influence entrepreneurial interest, this is in line with basic theory and research findings.